Natural crossbreeding between sympatric species of the Phyllosoma complex (Insecta: Hemiptera: Reduviidae) indicate the existence of only one species with morphologic and genetic variations - Martínez Hernandez, Fernando (2010)
The nucleotide sequences of the cytochrome B gene and the antennal phenotypes were analyzed for the following triatomine species: Triatoma longipennis, Triatoma pallidipennis, and Triatoma picturata, which belong to the Phyllosoma complex. These species inhabit sympatric areas from Talpa de Allende, Autlan de Navarro, and Teocuitatlan de Corona in Jalisco, Mexico. Molecular marker analysis showed that the sympatric individuals are the natural crossbred descendents of different individuals living in close proximity in these natural areas that resulted in mixed populations. The antennal phenotype results are coincident with these genetic findings, which point to the high similitude between all Phyllosoma complex populations analyzed. These data support the hypothesis that these species are morphotypes with chromatic and genetic varieties, which preserves the possibility of natural breeding with fertile descent. In conclusion, our results strongly support the hypothesis that T. pallidipennis, T. longipennis, and T. picturata are subspecies of the Phyllosoma complex.